Formation of Professional Pedagogical Activity of Future Physical Education Teachers in Educational Cluster Conditions - Sabirov Aloviddin Abdurakhmonovich (Web of Journals Publishing, 2023)
This article is about training future specialists in the conditions of the pedagogical education cluster, improving their professional and creative skills, which will be necessary for their future work, selecting talented students and determining their future creative activities, and in the "school-laboratory" field of experience. useful aspects of forming their professional activities are highlighted.
Keywords: professional activity, school-laboratory, pedagogical education cluster, conceptual, directing, creative abilities, gifted students, experimental sites, mutual cooperation, social cooperation.